The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1963
DOI: 10.1037/h0040525
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Study of obedience.

Abstract: This article describes a procedure for the study of destructive obedience in the laboratory. It consists of ordering a naive S to administer increasingly more severe punishment to a victim in the context of a learning experiment. Punishment is administered by means of a shock generator with 30 graded switches ranging from Slight Shock to Danger: Severe Shock. The victim is a confederate of the E. The primary dependent variable is the maximum shock the S is willing to administer before he refuses to continue fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
1,753
6
96

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 3,589 publications
(1,975 citation statements)
references
References 7 publications
22
1,753
6
96
Order By: Relevance
“…Observers often mistake situationally induced behavior as implying that others are evil, stupid, or weak willed, when in fact these individuals are good, decent individuals, just like us, who unwittingly succumb to the power of the situation. The most famous of these studies is Milgram's (1963) work on obedience to authority in which he demonstrated that individuals are willing to shock a complete stranger at high voltages when pressed by a scientific experimenter who insists that ''the experiment must continue''. Asch (1956) conducted conformity experiments in which participants gave conspicuously wrong answers to simple problems because other confederates, who were strangers to the participant, consistently gave the same wrong answer before the participant had an opportunity to respond.…”
Section: Power Of the Situation Over Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Observers often mistake situationally induced behavior as implying that others are evil, stupid, or weak willed, when in fact these individuals are good, decent individuals, just like us, who unwittingly succumb to the power of the situation. The most famous of these studies is Milgram's (1963) work on obedience to authority in which he demonstrated that individuals are willing to shock a complete stranger at high voltages when pressed by a scientific experimenter who insists that ''the experiment must continue''. Asch (1956) conducted conformity experiments in which participants gave conspicuously wrong answers to simple problems because other confederates, who were strangers to the participant, consistently gave the same wrong answer before the participant had an opportunity to respond.…”
Section: Power Of the Situation Over Behaviormentioning
confidence: 99%
“…1. Distribution of predicted and actual stopping voltages in the Milgram (1963) experiment. Psychiatrists (dark grey bars) and other normal individuals (light grey bars) made predictions about the voltage at which they thought they would stop if they were run through the experimental protocol.…”
Section: Self-processes Are Socialmentioning
confidence: 99%
“…Consider Harold Garfinkel's (1967) "breaching experiments," wherein researchers would consciously exhibit a contextually inappropriate behavior in a mundane social situation in order to observe the social reactions elicited by such behavior as well as (and more relevant to the notion of self-study) to gain experiential insight into the nature of violations of social expectations (Rafalovich, 2006). Stanley Milgram, famous for his Social Self-Experimentation 8 controversial studies on obedience to authority (Milgram, 1963), adopted Garfinkel's approach in several field experiments. These included a study into whether random strangers on New York City subways would give up their seats upon request to a covert experimenter, and while the study primarily focused on the reaction and compliance of the subway riders party to these requests, Milgram had his experimenters record and reflect on their own emotions, behavior, and psychological states during the interactions (Milgram, 2010b).…”
Section: A Brief History Of Psychological Self-experimentationmentioning
confidence: 99%
“…showing that 65% of a group of ordinary experimental subjects where willing to give another person electrical shocks up to 450 volts if prompted to do so by an experimenter the Milgram experiments have been widely discussed (Milgram, 1963). Some have subjected the experiments, and Milgram personally to severe criticism, whereas others have found the results disturbing but at the same time extremely enlightening.…”
Section: The Milgram Obedience Experiments From the Moment Stanley MImentioning
confidence: 99%
“…The first paper on the ethics of Milgram's research appeared only one year after the publication of Milgram's 1963 article. In this article two major problems in Milgram's design was identified and very harshly criticised.…”
Section: Deceptive Researchmentioning
confidence: 99%